MENINJAU KEABSAHAN LISENSI DAN PERLINDUNGAN HAK CIPTA ATAS SIARAN PERTANDINGAN SEPAK BOLA (STUDI KASUS PUTUSAN NO. 74 K/PDT.SUS-HKI/2017) - Ramos Adi Perisai (Fakultas Hukum Universitas Padjadjaran, 2023)
In Decision No. 74 K/Pdt.Sus-HKI/2017, Indonesian Supreme Court stated that PT Karya Teknik Hotelindo as the defendant had violated the copyright belonging to PT Inter Sport Marketing as the plaintiff for broadcasting 2014 World Cup football match as stated in the license agreement between PT Inter Sport Marketing and Federation International De Football Association. This article aims to understand the exactness of the Supreme Court in implementing copyright law on the case. This article employed legal research with the normative method which relies on data collection and data processing through literature study. This article reveals that there was misinterpretation from Supreme Court in defining an infringement towards copyright license belonging to PT Inter Sport Marketing and in qualifying football matches broadcast as the object of copyright protection.